The impact of sex hormones on genital wound healing in mice: a comparative study. Issue 6 (December 2019) - Chua, Michael E.; Rong, Mo; Tuba-ang, Karen; Silangcruz, Jan Michael A.; Tanseco, Patrick P.; Ming, Jessica Megan C.; Kim, Kyoung-Han; Hui, Chi Chung; Farhat, Walid A.
Summary: Introduction and objective: The effects estrogen and testosterone have on penile wound healing are still uncertain. This study evaluated the effects of these hormones on the wound healing process of penile and non-penile skin in wild-type ( Mus musculus  species) 4–5-week-old mice. Methodology: Seventy wild-type Mus musculus  species were randomly assigned to four groups control ( n  = 17), 1-week post-operative topical estrogen ( n  = 18), 1-week pre-operative testosterone ( n  = 17), and immediate post-operative testosterone ( n  = 18). Incisions were made on the ventrum of the penis and dorsal neck skin. On post-operative day 3, 7, and 14, incision sites were harvested. Evaluation was performed grossly for postsurgical penile edema and histologically for inflammatory cell concentration, presence of fibrinopurulent materials and distribution of collagen-fibroblastic cells. Each treatment group was compared at the three post-operative time points using the Fisher—Freeman--Halton exact test. CD34 and androgen receptor immunohistostaining was performed for between-group differences to assess microvascular density or vasodilatation and androgen receptor upregulation. Results: In this study, the experiment noted significant penile edema on post-operative day 7 in the testosterone groups, whereas less edema in the estrogen group ( P  = 0.010; Figure). On histologic evaluation of the penile wounds, a significantly increased inflammatory cell concentration was noted for both pre-operative and post-operative testosterone groups on post-operative day 14 ( P  = 0.023). The estrogen group revealed significantly increased fibrinopurulent material on the 3rd and 7th post-operative days ( P  = 0.045 and P  = 0.005, respectively). No significant between-group differences in the collagen-fibroblastic distribution were noted over the three-time phases. On histologic evaluation of the skin wounds, no significant differences were noted between the groups for inflammatory cell concentration and presence of fibrinopurulent materials. However, compared with the testosterone treatment groups, a significant higher collagen-fibroblast distribution was noted in the estrogen groups on post-operative day 3 and 14 ( P  = 0.001 and P  = 0.044,  respectively). Conclusion: Sex hormones, when given peri-operatively, may affect the wound healing process in mice. Testosterone appears to stimulate a prolonged inflammatory effect on penile wounds. Conversely, estrogen induces a fibrinopurulent congregation early in the penile wound healing process. For general skin healing, estrogen induces earlier collagen and fibroblast distribution, whereas testosterone has a delayed effect. The findings of this study should be further investigated in larger animal model with longer follow-up period. Summary Fig. Fig. 1